The Human Variome Project Beijing meeting. Issue 4 (12th April 2012) - Smith, Timothy D; Robinson, Helen M; Cotton, Richard G H
Abstract : The Human Variome Project Beijing Meeting, a joint meeting of the Human Variome Project Consortium and the Human Variome Project Chinese Node, was held in Beijing, 8th–12th of December, 2011. The aim of the Human Variome Project is to ensure that all information on genetic variation can be collected, curated, interpreted and shared freely and openly. The meeting officially welcomed the Human Variome Project Chinese Node as a partner of the Human Variome Project and focused on those areas where collaborations between China and the global Human Variome Project Consortium are required to develop and extend the coverage of international gene/disease specific databases.